Deflection behavior and fixity point location of piles in soft soil in Banjarmasin due to lateral force - Mardiyah, Ainul; Effendi, Rustam (CV. Literasi Indonesia, 2026)
Piles sometimes have to bear lateral loads that can generate lateral forces. These lateral forces cause deflections that can affect the position of the fixity point. Therefore, in this study, a modeling test was conducted to analyze the effect of pile stiffness (EI) variations on deflection values and fixity point locations. The research method involved creating a small-scale pile model with varying dimensions and specific loads. A test specimen in the form of a pile was subjected to lateral loads, and the deflection was then measured. The test results were further analyzed using MATLAB software to carefully analyze the pile deflection points and read the position of the fixity point. After conducting the research, it was concluded that the effect of pile stiffness (EI) variation on the deflection value for EI1 = 0.00012 kNm2 ranges from 0.19D to 0.86D; EI2 = 0.0003 kNm2 ranges from 0.16D to 0.66D, and EI3 = 0.00062 kNm2 ranges from 0.09D to 0.44D. The fixity point values range from EI1 = 0.00012 kNm2 ranging from 12.5D – 17.3D; EI2 = 0.0003 kNm2 ranging from 12D to 14D and EI3 = 0.00062 kNm2 ranging from 10.5D to 12D. Also, the eccentricity distance to the fixity point location value ranges from 3e to 3.6e, and the deflection value ranges from 0.1e to 0.17e.